2017
DOI: 10.1680/jgeot.16.p.049
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling and analysis of site liquefaction subjected to biaxial dynamic excitations

Abstract: The paper presents a series of centrifuge tests simulating a level site consisting of granular soil deposits subjected to various biaxial and uniaxial base excitations. The tests were conducted at RPI NEES centrifuge facility to assess the dynamic response characteristics of level deposits under multidirectional shaking. Synthetic sinusoidal waves were used as base excitations to test loose models under biaxial and uniaxial shaking. Dense arrays of accelerometers were used to monitor the deposit response along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…By using sinusoidal-type waveforms as input, they observed an increase of excess pore water pressure and postshaking settlement of 20% and 10%, respectively. More recently, El Shafee et al [13,14] and Cerna-Diaz et al [15] conducted similar tests on Nevada 120 and Ottawa 40/70 sand deposits, respectively. While El Shafee et al [13,14] used synthesized motions to simulate the phasetime history of real earthquakes, Cerna-Diaz et al [15] employed actual ground motion recordings with different levels of intensity.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…By using sinusoidal-type waveforms as input, they observed an increase of excess pore water pressure and postshaking settlement of 20% and 10%, respectively. More recently, El Shafee et al [13,14] and Cerna-Diaz et al [15] conducted similar tests on Nevada 120 and Ottawa 40/70 sand deposits, respectively. While El Shafee et al [13,14] used synthesized motions to simulate the phasetime history of real earthquakes, Cerna-Diaz et al [15] employed actual ground motion recordings with different levels of intensity.…”
Section: Introductionmentioning
confidence: 93%
“…More recently, El Shafee et al [13,14] and Cerna-Diaz et al [15] conducted similar tests on Nevada 120 and Ottawa 40/70 sand deposits, respectively. While El Shafee et al [13,14] used synthesized motions to simulate the phasetime history of real earthquakes, Cerna-Diaz et al [15] employed actual ground motion recordings with different levels of intensity. These studies showed that the increase in excess pore water pressure response during BD shearing may depend on the D r of the sand deposit, and that it can be as much as 100% higher than during UD shearing for the case of dense sands.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, there is another assumption in this research: only one plane of the drainage boundary is taken into consideration as shown in Figure 1. The influence of other planes remains to be explored by applying biaxial dynamic loading [21,22]. By controlling k i , the permeability of the drainage path can be simulated.…”
Section: Basic Concepts and Realization Of Different Drainage Conditionsmentioning
confidence: 99%
“…This method can be divided into three groups based on case histories during earthquakes that occurred in the past [14][15][16], the Arias intensity (I h ) [17,18], and laboratory test results [19,20]. Shafee et al [21] performed some uniaxial shaking tests and demonstrated that the difference between strain energy generated in the soil caused by biaxial and uniaxial shaking tests is negligible. Zheghal et al [22] studied the effect of non-proportionality and the phase angle of the induced shear stresses on rising pore water pressure.…”
Section: Introductionmentioning
confidence: 99%